Public awareness on sustainable transportation : a case study in Kuantan - Mohamad Zulfadhli, Che Hassim (2016)
Transportation is the one of the important element in living nowadays. Transport can make people easy in order to travel or move from one place to another place. However, if the transportation is not using in proper way it will lead to many problem like congestion and pollution. In Kuantan, the increasing in population caused the increasing in the usage number of transport especially private car and motorcycle. This situation affects the road traffic in Kuantan obviously during peak hour. Other than that, this situation also will cause the high environmental problem due to high fuel consumption by the transport. From the situation the study has been conducted to identify the awareness of people about sustainable transportation and to determine the relationship between the socioeconomic backgrounds towards readiness to switch to sustainable transport. In order to achieve the objective of the study the Chi-square method has been chosen to analyses the data. From the data analysis it is show that environmental awareness of people is high but they still choose not to use the sustainable transport. People seem more comfortable to use private transport than public transport. The results also show that people totally not ready to switch to walking or cycling and to reduce the car usage but they consider using the public transport as an alternative than using motor transport.